Pengaruh Disiplin dan Motivasi Terhadap Produktivitas Karyawan Pada PT. Boga Produce di Tangerang - Dede Andi (Mahesa Research Center, 2020)
This study aims to determine the effect of discipline and motivation on employee productivity at PT. Boga Produce in Tangerang. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, discipline has a significant effect on employee productivity by 39.2%, the hypothesis test is obtained t count> t table or (6,719> 1,994). Motivation has a significant effect on employee productivity by 54.6%, hypothesis testing is obtained t count> t table or (9.173> 1.994). Discipline and motivation simultaneously have a significant effect on employee productivity with the regression equation Y = 8.676 + 0.254X1 + 0.543X2 and the contribution of the influence is 57.9%, the hypothesis test obtained F count> F table or (47.424> 2.740).